Pengaruh Komitmen Organisasi dan Budaya Organisasi terhadap Kinerja Karyawan PT. Angkasa Pura I (PERSERO) Bandar Udara Internasional Adi Soemarmo Surakarta - Arizal Anwar; Apriatni Endang Prihatini (Universitas Diponegoro, 2016)
The research was distributed by growing companies in Indonesia namely manufacturing firm or company engaged in the service, one of these transport services. The growing demand for air transportation services in Indonesia. Along with the increased demand, human resources has a large role in determining the success of a service company. Thus required human resources that have a good performance so that it is able to serve the consumer well.The purpose of doing research is to know the influence of organizational commitment and organizational culture on performance of employees of PT Angkasa Pura I (Persero) international airport of Adi Soemarmo of Surakarta. The population was employees of PT Angkasa Pura I (Persero) international airport of Adi Soemarmo of Surakarta. While the samples used as much as 51 respondents with sampling techniques used was proportionate random sampling The analysis of the data used in this study using the SPSS program 23.0, test validity, reliability, determination of the coefficient of the correlation coefficient, regression analysis, simple and double, and the test of significance (t-test and F-test). in advance. The results of this study indicate that organizational commitment and organizational culture partially simultaneous or affect the performance of the employees. Variable cultural organizations provide greater influence on performance of employees on organizational commitment variable.The suggestions can be submitted is for PT. Angkasa Pura I (Persero) can hold a character building on a sense of love for the company to enhances the understanding of the vision and mission of the company so that the Organization's commitment to every employee of the higher. In addition, the company should put up posters about cultural organizations at each corner that are often bypassed the employees. This is intended so that employees always read and understand the organizational culture which is applied as a guide in the works.